Commissioning of the CMS High-Level Trigger with cosmic rays - Steinbrück, G.; Zeise, M.; Fischler, M.; Gutsche, O.; Chatrchyan, S.; Khachatryan, Vardan; Sirunyan, A. M.; Adam, Wolfgang; Arnold, B.; Bergauer, H.; Bergauer, Thomas; Dragicevic, Marko; et al. (IOP Publishing, 2010)
The CMS High-Level Trigger (HLT) is responsible for ensuring that data samples with potentially interesting events are recorded with high efficiency and good quality. This paper gives an overview of the HLT and focuses on its commissioning using cosmic rays. The selection of triggers that were deployed is presented and the online grouping of triggered events into streams and primary datasets is discussed. Tools for online and offline data quality monitoring for the HLT are described, and the operational performance of the muon HLT algorithms is reviewed. The average time taken for the HLT selection and its dependence on detector and operating conditions are presented. The HLT performed reliably and helped provide a large dataset. This dataset has proven to be invaluable for understanding the performance of the trigger and the CMS experiment as a whole.
Keywords: Trigger concepts and systems (hardware and software); Online farms and online filtering; Compact Muon Solenoid; Physics - Instrumentation and Detectors; online filtering; FOS: Physical sciences; Large Hadron Collider (LHC); Physical sciences; Online farms and online filtering; Particle physics; Large hadron collider; CMS; Subatomär fysik; Online farm; CMS; LHC; High Level Trigger; Subatomic Physics; [PHYS.PHYS.PHYS-INS-DET]Physics [physics]/Physics [physics]/Instrumentation and Detectors [physics.ins-det]; Detectors and Experimental Techniques; info:eu-repo/classification/ddc/530; Trigger concepts and systems; info:eu-repo/classification/ddc/610; CMS; Physics; CMS high-level trigger; ddc:530; cosmics; Instrumentation and Detectors (physics.ins-det); High Level Trigger; Large hadron collider; Cosmic Run At Four Tesla (CRAFT); LHC; CMS; Muoni; Physics and Astronomy; Trigger concepts and systems (hardware and software); [PHYS.PHYS.PHYS-INS-DET] Physics [physics]/Physics [physics]/Instrumentation and Detectors [physics.ins-det]; High-Level Trigger; Instrumentation; Mathematical Physics; Particle physics; LHC; Online farms and